Peran E-Commerce dalam Meningkatkan Daya Saing Usaha Lokal di Kota Bima: Studi Usaha Tenun Songket Nur Sakura Kota Bima - Rahmah; Rafiuddin; Muhammad Zia Ulhaq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to understand the role of e-commerce in enhancing the competitiveness of local businesses in Bima City. The business actor referred to in this research is the Nur Sakura woven textile shop in Bima City. This study uses a qualitative approach with a case study strategy. Data collection techniques include observation, interviews, and direct documentation of the related object. Data validity techniques use triangulation. The results of the study show that e-commerce plays a significant role for entrepreneurs, especially for local Micro, Small, and Medium Enterprises (MSMEs), in this case for the Nur Sakura woven textile shop in Bima City. By leveraging this technology, MSMEs can expand their market reach globally without geographical limitations, improve operational efficiency, and enhance their competitiveness in an increasingly digital market. By implementing e-commerce promotion strategies, MSMEs can boost their online presence, reach more customers, and increase their sales. This will help them compete in an increasingly digital market and strengthen their competitiveness in the long term. The conclusion of this study is that the use of e-commerce can enhance the competitiveness of Nur Sakura's woven textiles in both national and international markets.